استخدام استراتيجيات تعلم المفردات لدى الناطقين بغير العربية بالجامعة الإسلامية العالمية بماليزيا - Rabi'atul Aribah binti Muhamad Isa @ Omar (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study aims to investigate the vocabulary learning strategies used by Arabic leaners at the International Islamic University Malaysia. It also compares between the Arabic and non- Arabic majoring students in the use of these strategies. The sample of this study was 313 students from different levels of study. The completed a 'Vocabulary Learning Strategies Questionnaire' by Pavicic Takac (2008) which consisted of three different components: Formal strategies, self- initiated independent strategies and incidental strategies. The results indicate that Arabic learners used a variety of vocabulary learning strategies with using dictionary being the most widely employed. No statistically significant difference was found between the Arabic and non-Arabic majoring learners. The findings provide support in helping students to utilize their mother tongue in a fruitful way to learn new vocabulary as well as train both groups equally on how to use these strategies efficiently.